Odpowiedź :
a)-3+3razy2=3
b)2razy10-10=10
c)3razy-1+12=9
d)4razy2-2=6
e)2razy5-2razy1½=7
f)0,4razy2+0,3razy2=1,4
g)2razy4+3razy2=14
w równaniach niżej wystarczy podstawić liczby i wyjdą wyniki:)
b)2razy10-10=10
c)3razy-1+12=9
d)4razy2-2=6
e)2razy5-2razy1½=7
f)0,4razy2+0,3razy2=1,4
g)2razy4+3razy2=14
w równaniach niżej wystarczy podstawić liczby i wyjdą wyniki:)
1)x+3y=3
x-y=5
x+3y=3
x=5+y
5+y+3y=3
4y=-2
y=-1/2
x=5+(-1/2)=4,5
2)2x-y=10
x+5y=-17
2x-y=10
x=-17-5y
2(-17-5y)-y=10
-34-10y-y=10
-11y=44
y=-4
x=-17+20=3
3)3m+n=9
2m-5n=-11
n=9-3m
2m-5n=-11
2m-5(9-3m)=-11
2m-45+15m=-11
17m=34
m=2
n=9-6=3
d) 4a-2=b
3a+7b=1,5
3a+7(4a-2)=1,5
3a+28a-14=1,5
31a=15,5
a=2
b=8-2=6
e) 2x-2y=7
4x+3y=21
2x=7+2y
4x+3y=21
x=3,5+y
4x+3y=21
4(3,5+y)+3y=21
14+4y+3y=21
7y=7
y=1
x=3,5+1=4,5
f) 0,4x+0,3y=1,4
0,1x+3y=2,3
4x+3y=14
x+30y=23
4x+3y=14
x=23-30y
4(23-30y)+3y=14
92-120y+3y=14
-117y=-78
y=0,7
x=23-21=2
g)2x+3y=14
3x-2y=8
2x=14-3y
3x-2y=8
x=7-1,5y
3x-2y=8
3(7-1,5y)-2y=8
21-4,5y-2=8
-6,5y=-13
y=2
x=7-3=4
x-y=5
x+3y=3
x=5+y
5+y+3y=3
4y=-2
y=-1/2
x=5+(-1/2)=4,5
2)2x-y=10
x+5y=-17
2x-y=10
x=-17-5y
2(-17-5y)-y=10
-34-10y-y=10
-11y=44
y=-4
x=-17+20=3
3)3m+n=9
2m-5n=-11
n=9-3m
2m-5n=-11
2m-5(9-3m)=-11
2m-45+15m=-11
17m=34
m=2
n=9-6=3
d) 4a-2=b
3a+7b=1,5
3a+7(4a-2)=1,5
3a+28a-14=1,5
31a=15,5
a=2
b=8-2=6
e) 2x-2y=7
4x+3y=21
2x=7+2y
4x+3y=21
x=3,5+y
4x+3y=21
4(3,5+y)+3y=21
14+4y+3y=21
7y=7
y=1
x=3,5+1=4,5
f) 0,4x+0,3y=1,4
0,1x+3y=2,3
4x+3y=14
x+30y=23
4x+3y=14
x=23-30y
4(23-30y)+3y=14
92-120y+3y=14
-117y=-78
y=0,7
x=23-21=2
g)2x+3y=14
3x-2y=8
2x=14-3y
3x-2y=8
x=7-1,5y
3x-2y=8
3(7-1,5y)-2y=8
21-4,5y-2=8
-6,5y=-13
y=2
x=7-3=4
a)
x+ 3y = 3
x - y = 5
x=3-3y
3-3y-y=5
x=3-3y
-4y=2 /:(-4)
y=1/2
x=3-1½
y=1/2
x=1½
b)
2x - y = 10
x+5y = - 17
-y=10-2x /*(-1)
x+5y = - 17
y=-10+2x
x-50+10x = - 17
y=-10+2x
x-50+10x = - 17
y=-10+2x
11x = 35
y=-10+2x
x=3 i 2/11
y=-10+6 i 4/11
x=3 i 2/11
y=-3 i 7/11
x= 3 i 2/11
c)
3m + n = 9
2m - 5n = - 11
n=9-3m
2m-45+15m=-11
n=9-3m
17m=34
n=9-3m
m=2
n=9-6
m=2
n=3
m=2
d)
4a - 2 = b
3a + 7b = 1,5
b=4a-2
3a+28a-14=1,5
b=4a-2
31a-14=1,5
b=4a-2
a=½
b=0
a=½
e)
2x - 2y = 7 /:2
4x + 3y = 21
x=3,5+y
14+4y+3y=21
x=3,5+y
7y=7
x=3,5+y
y=1
x=4,5
y=1
f)
0,4x + 0,3y = 1,4 /*10
0,1x + 3y = 2,3 /*10
4x+3y=14
x=23-30y
92-120y+3y=14
x=23-30y
-117y=-78
x=23-30y
y=2/3
x=3
g)
2x + 3y = 14
3x - 2y = 8 /:2
2x + 3y = 14
1,5x - y = 4
2x + 3y = 14
y = -4-1,5x
2x -12 -4,5x = 14
y = -4-1,5x
-2,5x=26 /:(-2,5)
y = -4-1,5x
x=-10,4
y = -4-15,6
x=-10,4
y =-19,6
Mam nadzieje że dobrze
x+ 3y = 3
x - y = 5
x=3-3y
3-3y-y=5
x=3-3y
-4y=2 /:(-4)
y=1/2
x=3-1½
y=1/2
x=1½
b)
2x - y = 10
x+5y = - 17
-y=10-2x /*(-1)
x+5y = - 17
y=-10+2x
x-50+10x = - 17
y=-10+2x
x-50+10x = - 17
y=-10+2x
11x = 35
y=-10+2x
x=3 i 2/11
y=-10+6 i 4/11
x=3 i 2/11
y=-3 i 7/11
x= 3 i 2/11
c)
3m + n = 9
2m - 5n = - 11
n=9-3m
2m-45+15m=-11
n=9-3m
17m=34
n=9-3m
m=2
n=9-6
m=2
n=3
m=2
d)
4a - 2 = b
3a + 7b = 1,5
b=4a-2
3a+28a-14=1,5
b=4a-2
31a-14=1,5
b=4a-2
a=½
b=0
a=½
e)
2x - 2y = 7 /:2
4x + 3y = 21
x=3,5+y
14+4y+3y=21
x=3,5+y
7y=7
x=3,5+y
y=1
x=4,5
y=1
f)
0,4x + 0,3y = 1,4 /*10
0,1x + 3y = 2,3 /*10
4x+3y=14
x=23-30y
92-120y+3y=14
x=23-30y
-117y=-78
x=23-30y
y=2/3
x=3
g)
2x + 3y = 14
3x - 2y = 8 /:2
2x + 3y = 14
1,5x - y = 4
2x + 3y = 14
y = -4-1,5x
2x -12 -4,5x = 14
y = -4-1,5x
-2,5x=26 /:(-2,5)
y = -4-1,5x
x=-10,4
y = -4-15,6
x=-10,4
y =-19,6
Mam nadzieje że dobrze